Visual and Rapid Diagnosis of Neisseria gonorrhoeae Using Loop-Mediated Isothermal Amplification Combined With a Polymer Nanoparticle–Based Biosensor in Clinical Application - Chen, Xu; Zhou, Qingxue; Wu, Xueli; Wang, Shuoshi; Liu, Rui; Dong, Shilei; Yuan, Wei (Frontiers in Molecular Biosciences, 2021)
Neisseria gonorrhoeae is a host-adapted human pathogen that causes sexually transmitted gonorrhea, and remains to be a serious global public health challenge, especially in low- and middle-income regions. It is vital to devise a reliable, simple, cost-saving, and easy-to-use assay for detecting N. gonorrhoeae agent. In the current study, we firstly report a novel approach, loop-mediated isothermal amplification linked with polymer nanoparticle-based biosensor (LAMP-PNB), was used for identifying of N. gonorrhoeae in clinical samples. The results showed that The LAMP primers based on the orf1 gene were valid for development of N. gonorrhoeae-LAMP-PNB assay. The detection system with optimal conditions could be performed at a fixed temperature 64℃ for 40 min. The whole process, including genomic DNA preparation (approximately 10 min), LAMP reaction (40 min), and PNB reporting (approximately 2 min), could be accomplished within 60 min. The limited of detection (LoD) of N. gonorrhoeae-LAMP-LFB assay was 50 copies per test. The specificity of current assay was one hundred percent, and no cross-reactions to non-N. gonorrhoeae isolates were observed. These results confirmed that the N. gonorrhoeae-LAMP-PNB technique is a reliable, specific, sensitive, rapid, low-cost, and easy-to-use method for detecting gonococci isolates. More importantly, this assay has great potential to develop a point-of-care (POC) testing in clinical practice, especially in resource-constrained regions.